Literature Review: Penerapan Model Pembelajaran Project Based Learning (PjBL) terhadap Hasil Belajar dalam Mata Pelajaran Ekonomi Siswa SMA - Dwiyanti, Anisa; Nursidiq, Cahyana (Literasi: Jurnal Ilmu Pendidikan, 2026)
His study aims to examine the effectiveness of the Project Based Learning (PjBL) model on high school students' learning outcomes in economics. The issue addressed is the low academic achievement among students and the need for innovative teaching methods that promote critical thinking and active engagement. The research employs a Systematic Literature Review (SLR) method, analyzing five scientific articles published between 2021 and 2025. The findings indicate that the implementation of PjBL has a positive impact on student learning outcomes, particularly in enhancing motivation, conceptual understanding, as well as critical and collaborative thinking skills. However, the effectiveness of PjBL largely depends on teacher readiness, student motivation, and the supportiveness of the learning environment. With proper preparation and guidance, PjBL has the potential to become an effectiv.Keywords: Project Based Learning, learning outcomes, economics, high school students.